Impacts of Industrial Agglomeration and Energy Intensity on Industrial Eco-Efficiency-Analysis Based on Spatial Correlation and Mediating Effect - Zhong, Cheng; Hamzah, Hanny Zurina; Yin, Jin; Wu, Desheng; Cao, Jianhong; Mao, Xiaoming; Zhuang, Qianda (Frontiers in Environmental Science, 2022)
As a measuring tool of industrial sustainable development, industrial eco-efficiency works as a link between economic benefit and environmental pressure. Industrial agglomeration and energy have always been considered important influence factors on industrial eco-efficiency. For China facing the challenge of reaching a Carbon Peak by the 2060s, it is critically important to explore the relationship between industrial agglomeration and industrial eco-efficiency, and energy intensity may play a key role between them, which should not be ignored. Therefore, based on the STIRPAT model, this paper constructs a spatial autocorrelation model to analyze the provincial panel dataset from 2009 to 2018, and it is found that: First, the industrial agglomeration has an inverted N-shape relationship with industrial eco-efficiency, and industrial eco-efficiency indeed have a positive spatial spillover effect. Second, energy intensity plays a mediating role, industrial agglomeration would affect industrial eco-efficiency through energy intensity. Therefore, it is suggested that the government should introduce differentiated industrial agglomeration policies as well as energy-saving policies. In addition, consistent industrial sustainable development policies should be adhered to in the adjacent areas.